ELAVL1 Regulates NLRP3 Inflammasome Activation and Contributes to Diabetic Hypoglycemia-Related Myocardial Injury - Xiao Wei; Bo Zhou; Shiwei Chen; Feng Xie (Discovery Medicine, 2026)
Background: Recurrent hypoglycemia is a common complication of intensive glycemic control in patients with type 2 diabetes mellitus and may contribute to cardiovascular injury. However, the molecular mechanisms underlying hypoglycemia-induced myocardial inflammation remain incompletely understood. This study aimed to elucidate the function and mechanistic pathways by which the RNA-binding protein ELAV-like RNA binding protein 1 (ELAVL1, also termed Hu antigen R / HuR) modulates NLRP3 pathway-associated inflammatory responses in the context of myocardial injury exacerbated by recurrent hypoglycemia in type 2 diabetes mellitus.Methods: A total of eighteen male C57BL/6J mice were allocated at random into three experimental groups (n = 6 per group): a control group, a type 2 diabetes mellitus group generated by high-fat feeding followed by streptozotocin administration, and a diabetic hypoglycemia group, in which diabetic mice received daily intraperitoneal insulin treatment for five consecutive days to establish recurrent hypoglycaemic episodes. Hypoglycemia was defined as a blood glucose concentration of ≤3.5 mmol/L maintained for 1 h. Cardiac function was assessed by echocardiography. Myocardial histopathology was examined by hematoxylin–eosin staining. Serum concentrations of cardiac troponin I (cTnI), cTnT, interleukin-1β (IL-1β), IL-18, and insulin were quantified using enzyme-linked immunosorbent assay (ELISA). Myocardial ELAVL1 mRNA expression was quantified by quantitative real-time PCR (qPCR). An intermittent low-glucose/recovery model was established in HL-1 atrial cardiomyocytes. ELAVL1 expression was silenced (sh-ELAVL1) or overexpressed (oe-ELAVL1) using lentiviral vectors. Cell injury was evaluated by CCK-8 assay and lactate dehydrogenase (LDH) release. The transcript and protein abundance of ELAVL1, NLRP3, and cleaved caspase-1 (p20) were determined using qPCR and immunoblot analysis, whereas GSDMD-N (p30) expression was visualized by immunofluorescence.Results: HDM mice demonstrated greater reductions in left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS) than diabetes mellitus (DM) controls (p < 0.05), with more severe myocardial fiber disorganization, interstitial edema, and inflammatory cell infiltration. The HDM group displayed markedly higher circulating concentrations of cTnI, cTnT, IL-1β, and IL-18, together with increased myocardial ELAVL1 transcript abundance (p < 0.05). In vitro, recurrent hypoglycemic stimulation reduced cell viability and increased LDH release (p < 0.05), accompanied by upregulation of ELAVL1 and NLRP3 expression. ELAVL1 silencing restored cell viability, reduced LDH release, and decreased the expression of NLRP3, cleaved Caspase-1 (p20), and GSDMD-N (p30) (p < 0.05), whereas ELAVL1 overexpression exerted the opposite effects (p < 0.05).Conclusion: Recurrent hypoglycemia exacerbates myocardial injury in diabetic mice and is accompanied by enhanced inflammatory responses and increased ELAVL1 levels. In vitro functional studies further demonstrated that ELAVL1 positively regulates NLRP3/Caspase-1/gasdermin D (GSDMD)-associated pyroptotic signaling and aggravates hypoglycemia-induced cardiomyocyte injury. These findings suggest that ELAVL1 may contribute to the pathogenesis of diabetes-associated hypoglycemic myocardial injury and represents a potential therapeutic target.